RESEÑA de : Borderías Uribeondo, M. P. & Muguruza Cañas, M. C.: Impacto Ambiental. Madrid: 2014, UNED. - Aguilera Arilla, M.ª José (Espacio Tiempo y Forma. Serie VI, Geografía, 2015)
RESEÑA de : Borderías Uribeondo, M. P. & Muguruza Cañas, M. C.: Impacto Ambiental. Madrid: 2014, UNED.